Promoting a sense of belonging in university online learning: How and why initial teacher education students experience an increased sense of belonging - Adlington, Rachael; O'Neill, Kristy; Volpe, Catherine Rita; Harrington, Ingrid (Australasian Journal of Educational Technology, 2024)
Despite evidence of practices that support online students in university learning, promoting engagement and building a student sense of belonging continue to be a challenge. To enhance student engagement, a suite of evidence-based learning design strategies was incorporated across online units of study in initial teacher education programmes at a regional Australian university. To determine the impact of these strategies or elements, students were surveyed regarding their perspectives on how the elements had positively impacted their sense of belonging within the online university community. The systemic functional linguistics Appraisal framework was used to analyse qualitative survey data, which reported students experienced an increased sense of belonging expressed as positive judgements of their own mental capacities. Students also expressed feeling cared for, valued and supported by academics and experienced enjoyment in their learning and reduced levels of stress. All elements were positively evaluated; however, unit coordinator behaviour, especially social capacity, was unexpectedly important in increasing student sense of belonging. Whilst ongoing incorporation of design elements to enhance engagement is important, the behaviours of unit coordinators actioned through these elements were paramount in promoting student belonging. Implications for practice or policy: Increasing levels of student belonging may be improved by including learning experiences that promote feelings of success and relationships with others. Unit coordinators can enhance online student belonging by using online learning design elements to demonstrate approachability, understanding, supportiveness, availability, presence, care and patience. Universities should consider adopting organisation-wide initiatives that promote consistent and visible learning design features and staff presence, with the aim of addressing attrition and retention challenges.